Midterm Analysis of Survival and Cause of Death Following Endovascular Abdominal Aortic Aneurysm Repair. (July 2017) - Healy, Gerard M.; Redmond, Ciaran E.; Gray, Sam; Iacob, Lucian; Sheehan, Stephen; Dowdall, Joseph F.; Barry, Mary; Cantwell, Colin P.; Brophy, David P.
Purpose: To assess rates of complications, secondary interventions, survival, and cause of death following endovascular abdominal aortic aneurysm (AAA) repair over a 10-year period. Materials and Methods: Single-institution retrospective cohort study of all patients undergoing primary endovascular aortic aneurysm repair (EVAR) between July 2006 and June 2015. The population constituted 175 patients with 163 fusiform and 12 saccular AAAs. Of these, 149 (85%) were male, with mean age 75.4 (±7.1) years. Patients were followed up until June 30, 2016. Cause of death was determined from the national death register. Results: Mean follow-up was 34.4 (±24.4) months. The secondary intervention rate was 9.7%, and there were 4 aneurysm ruptures (0.8% annual incidence). Thirty-day mortality was 0.6%. Survival at 1, 3, and 5 years was 93.1%, 84%, and 64.9%, respectively. Forty-eight patients died during follow-up, 3 secondary to rupture, leading to overall and aneurysm-related death rates of 9.7 and 0.6 per 100 person-years. All other deaths were due to nonaneurysm causes, most commonly cardiovascular (n = 15), pulmonary (n = 13), and malignancy (n = 9). Baseline renal impairment ( P < .001), ischemic heart disease ( P < .05), age greater than 75 years ( P < .05), and urgent/emergency EVAR were associated with inferior long-term survival. Type II endoleak negatively influenced fusiform aneurysm sac regression ( P = .02), but there was no association between survival and occurrence of any complication or secondary intervention. Conclusion: The majority of deaths during medium-term follow-up post-EVAR are due to nonaneurysm-related causes. Survival is determined by the following baseline factors: renal impairment, ischemic heart disease, advanced age, and the presence of a symptomatic/ruptured aneurysm.